2020
DOI: 10.1016/j.heliyon.2020.e04629
|View full text |Cite
|
Sign up to set email alerts
|

How stressful life events and violence are related to mental health: the protective role of social relations in African context

Abstract: Adolescents are universally expected to be at risk for heightened stress and violence, and subsequently to mental health problems. Good social relationships may protect their mental health, but research has mainly focused on singular relations, such as peer popularity or general social support. The current study analyses the buffering role of multiple relationships in an African context. First, how stressful life-events and violent experiences are associated to mental health, and, second, whether good social r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 78 publications
(101 reference statements)
0
6
0
1
Order By: Relevance
“…Health authorities, however, in most countries, including Bangladesh, mainly focus on controlling the number of new cases and deaths to a minimum, but psychological distress and its associated reverberations are often overlooked. Psychological distress does not emerge only from the panic of being infected with COVID-19; several other factors also play rigorous roles ( Islam, Bodrud-Doza, Khan, Haque, & Mamun, 2020 ; Mahmud et al, 2020 ; Nyarko, Peltonen, Kangaslampi, & Punamäki-Gitai, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Health authorities, however, in most countries, including Bangladesh, mainly focus on controlling the number of new cases and deaths to a minimum, but psychological distress and its associated reverberations are often overlooked. Psychological distress does not emerge only from the panic of being infected with COVID-19; several other factors also play rigorous roles ( Islam, Bodrud-Doza, Khan, Haque, & Mamun, 2020 ; Mahmud et al, 2020 ; Nyarko, Peltonen, Kangaslampi, & Punamäki-Gitai, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fenomena kekerasan disebabkan banyak faktor, salah-satu di antaranya ialah kemiskinan dan ketidakadilan sosial (Caruso & Schneider, 2011;Khattab et al, 2018), fundamentalisme agama (Ellis, 2017), dan prasangka sosial (Rowatt & Al-Kire, 2021). Kekerasan sangat berdampak pada suasana psikologis individu yakni stres (Nyarko et al, 2020;Binder et al, 2020) dan perasaan traumatik (Steel et al, 2009). Uniknya, belakangan ini konsentrasi penelitian psikologi cukup besar membahas perilaku negatif dibanding menonjolkan aspek positif dari perilaku manusia (Sumanto, 2006).…”
Section: A Pendahuluanunclassified
“…Violence or abuse is intense negative stress (70). Moreover, cumulating evidence showed that abused parents are at increased risk for perpetuating maladaptive parenting practices, which would be transmitted to generations to come through not just intimate (71,72), but also the underlying uncontrollable epigenetic mechanisms (73).…”
Section: Violence and Abusementioning
confidence: 99%